Promotion of European wines in third countries within the common market organisation framework: The case of France - Angelo Puccia; César M. Mora Márquez; Julia M. Nú\~nez-Tabales (Economies, 2022)
The international wine market has undertaken important structural changes in the first decades of the 21st century, both in terms of demand and offer. In order to mitigate the effect deriving from the increase in competition, the European Union (EU) continues to allocate important resources to increase the competitiveness of the winemaking sector by means of its Common Agricultural Policy (CAP) and the Common Market Organization (CMO). This paper aims to understand which factors have an influence on the correct implementation of the CMO measure of promotion in the principal wine exporter country: France. A fuzzy-set model (fs/QCA) has been utilized, studying a period of 10 years since 2009. Results show that is it possible to obtain a better execution ratio of measure of promotion by adapting some key factors, such as CMO budget allocation. These findings could support French national and regional authorities in the task of planning. Moreover, other Member States (MS) could also benefit, since in the new CAP approach, a higher participation in strategic plans is required for them by the EU.
Keywords: 330; Common Agricultural Policy; Common Market Organization; measure of promotion; third countries; wine; wineries